TRENDS OF SADFISHING PHENOMENON AND DISAPPEARANCE OF SELF-PRIVACY ON SOCIAL MEDIA TIKTOK - Ramadhani, Annisa Putri; Putri, Citra Eka; Hamzah, Radja Erland (Journal of Social Political Sciences, 2022)
Content creators are competing to increase viewers and enter the TikTok homepage or commonly known as FYP (For Your Page). The existence of this FYP encourages content creators to start doing something that makes their TikTok account viral, one of which is creating sad content or sadfishing. Sadfishing has become a trend where this trend occurs because artists, actors or even ordinary characters share unimportant sadness to get the attention of many people so that they will feel satisfied and are encouraged to continue to sell their sad stories to bring fame. This study uses the basic concept of sadfishing and Dramatism Theory. The approach in this research is qualitative with case study research method. The data collection technique was carried out by in-depth interviews. The data analysis technique uses a method that is carried out in three stages, namely: data reduction, data presentation, and conclusions or verification as a technique for compiling research. The results show that influencers who own TikTok accounts share sadness or Sadfishing because of the "Trend" insistence on TikTok Social Media in order to gain sympathy and empathy, content creators will increasingly look for ways to keep their content liked by many people. the point of it all is that they just want to go viral and be famous.